An Empirical analysis on Japan's industrial hollowing out - SHIN, Saemee (KDI School, 2022)
The purpose of this study is to investigate the role of domestic factors in hollowing out of Japan''s manufacturing industry. During the three lost decades, Japan''s manufacturing, an indicator of its economic health, suffered from the deterioration of international competitiveness. The rise in competition with emerging countries and domestic production costs forced Japanese manufacturers to operate overseas, hurting manufacturing value-added and employment. Among internal factors that caused Japan''s industrial hollowing out, several episodes of yen appreciations have fostered not only economic recessions brought on by weakening exports but the deindustrialization of Japanese manufacturing since the late 1980s. This paper exploits aggregate time-series data from 1960 to 2021 to verify the increase in outward FDI and value of yen, a collapse of export-led growth along with Chinese economic expansion, and TFP growth has prompted deindustrialization in Japan. The paper also investigates the effect of sectoral exports, FDI outflows, and yen exchange rate fluctuations on the manufacturing share of GDP, using industry-specific data from 1970 to 2021.
Thesis(Master) -- KDI School: Master of Public Policy, 2022
Keywords: Manufacturing industries--Japan; Industrial policy--Japan